Community medicine clerkship amidst COVID-19 pandemic: re-designing, implementation, and evaluation - Tyastuti, Dwi; Risahmawati, Risahmawati; Fadhillah, Marita; Ekayanti, Fika; Kunarisasi, Sity; Azwar, Ahmad (International Journal of Practice-based Learning in Health and Social Care, 2023)
Clerkship on primary care and family medicine is multi-elemental and very challenging in amidst the COVID-19 pandemic. Some medical students have postponed their graduation because the clerkship at the health center cannot be carried out in a pandemic situation. This article aims to describe the community medicine clerkship (CMC) module and how the implementation amidst the COVID-19 pandemic. This module was delivered by online and offline activities from 10th August to 13th September 2020. A total of forty students, twelve faculty mentors, and fifteen PHC preceptors from ten PHCs in Tangerang District, Indonesia were involved. Students could carry out activities and fulfill assignments given in the midst of a pandemic with a re-designing of the CMC module. One-sample t-tests were run to determine whether scores of students participating in CMC module during the COVID-19 pandemic differed from normal and showed that individual and group scores were significantly different from normal. The findings of the study clearly indicate that all clinical clerkship modules must be redesigned to suit the current conditions. Modifications and variations of various learning methods, guidance techniques, monitoring and coordination are factors that should be considered in its implementing.